Making Jesus Christ Visible as a Jew in the Celebration of the Eucharist - Rutishauser, S.J., Christian M. (Studies in Christian-Jewish Relations, 2026)
The Roman Catholic liturgy, as celebrated today since the reform of the Second Vatican Council, has overcome anti-Judaism. This essay shows that it does not, however, take into account Jesus' Jewishness and the renewed theological teaching that Israel continues to stand in an unrevoked covenant with God. It describes how the commemoration of the history of salvation, which takes seriously the Jewishness of Jesus and the continuing election of Israel, can be presented in the prayers and prefaces, as well as through the commemoration of saints and the adaptation of the lectionary. A revised restoration of the Feast of the Circumcision of Jesus or a further development of the Creed are proposed.